The Relationship Between Family Support and Adherence to Taking Medication in Pulmonary TB - Namuwali, Domianus; Hara, Maria Kareri; Nurwela, Trifonia Sri; Banhae, Yulianti Kristiani (GLOBAL HEALTH SCIENCE GROUP, 2023)
Pulmonary TB is still a current health problem that needs serious attention, this disease is the main cause of death due to infectious diseases. Globally, in 2021 it is estimated that 10 million people worldwide will suffer from pulmonary TB. To increase the scope of recovery, patients need family support while the patient is undergoing pulmonary TB treatment. Objective: This study aims to determine family support for treatment compliance in pulmonary TB sufferers at the Waingapu City Health Center. Research Method: This study used a cross-sectional approach to examine the relationship between family support and treatment adherence in pulmonary TB sufferers at the Waingapu Community Health Center. The population in this study was all pulmonary TB patients seeking treatment at the Wainga Community Health Center, totaling 61 people. Sampling was carried out non-randomly using total sampling technique. Collection was carried out by distributing questionnaires to pulmonary TB sufferers who visited the Waingapu Health Center. This research was carried out at the Waingapu Community Health Center in May – July 2023. Data analysis was carried out univariately and bivariately using Cotingency Coefficient analysis to determine the relationship between family support and compliance with taking medication for pulmonary TB sufferers at the Waingpu Community Health Center. Data analysis was carried out univariately and bivariately using Cotingency Coefficient analysis to determine the relationship between family support and compliance with taking medication for pulmonary TB sufferers at the Waingpu Community Health Center. Research Results: The research results showed that 57 people (93.4) had good family support and 4 people (6.6%) had poor family support. They were compliant with taking pulmonary TB medication. As many as 56 (91.6%) while 5 people (8.2%) did not comply with taking pulmonary TB medication. Based on the results of the Contingency Coefficient test, the P value was 0.536, which means there is no relationship between family support and compliance with taking medication for pulmonary TB sufferers at the Waingapu Community Health Center. Conclusion: There is no relationship between family support and medication adherence for pulmonary TB sufferers at the Waingapu Community Health Center.